Predictors of Favorable Angiographic Outcomes After Drug-Coated Balloon Use for de novo Small Vessel Coronary Disease (DCB-ONLY). (November 2021) - Kang, Woong Chol; Park, Sang Min; Jang, Albert Youngwoo; Oh, Pyung Chun; Shin, Eun-Seok; Yu, Cheol Woong; Oh, Seung-Jin; Kim, Yong Hoon; Won, Hoyoun; Lee, Sang-Rok; Lee, Sang Yeub; Hong, Young Joon; et al.
We evaluated the angiographic parameter and clinical outcomes of drug-coated balloon (DCB) to assess the optimal angiographic criteria in de novo small vessel disease (SVD). Patients (n = 424, mean age: 64.4 ± 11.2 years, men: 69.8%) at 20 sites in Korea were prospectively enrolled. The primary end point was late luminal loss (LLL) at 9-month follow-up angiography. Secondary end points included restenosis rates, target lesion failure (TLF), and DCB-related thrombosis during the 12-month follow-up period. We included 403 patients for analysis excluding 21 patients who required bailout stenting. Baseline mean reference vessel .diameter was 2.52 ± 0.39 mm and mean minimal luminal diameter (MLD) was 0.71 ± 0.40 mm. The mean MLD was 1.54 ± 0.37 mm after DCB. Late luminal loss was −0.01 ± 0.43 mm and restenosis was noted in 26 patients (12.2%). Minimal luminal diameter >1.6 mm and % diameter stenosis ( DS ) <45% after DCB was associated maintenance of MLD without LLL at 9-months. Multivariate analysis demonstrated that %DS at baseline and post-MLD was associated with the restenosis. During 12-month follow-up, TLF was 2.6% including 1 cardiac death, 1 myocardial infarction, and 10 ischemia-driven target lesion revascularizations. Drug-coated balloon showed a low restenosis and lower LLL despite high in-segment DS. Post-MLD and % DS may be helpful to get optimal results in de novo SVD after DCB.